Effect of Swarna Prashana (Oral Administration of Gold as Electuary) in Children: A Conceptual Study. - Kumar, Hitesh; Prasad, Mahendra (International Research Journal of Ayurveda & Yoga, 2023)
A type of electuary that falls under the heading of pediatrics is described in the classics of Ayurveda as Swarna Prashana (oral administration of gold as electuary). In the Kashyapa Samhita, it is intended to aid infants’ memory, intuition, and invulnerability. It is depicted in terms of Jatakarma Samskara, or new-born consideration. One of the 16 basic Samskaras that Ayurveda describes. As an illustration of how Swarna Prashana satisfies the main tenets of Ayurveda, see preventative measures. Vyadhikshamtva (immunity) is our body’s propensity to detect the microscopic organisms that propagate disease and are responsive or losing their potency. The main topic of discussion in the medical industry has historically been how to prevent disease by boosting immunity, and these days, swarna prashana serves as an oral resistance booster (oral antibody). The current conceptual study demonstrates how Swarnaprashana improves immunity while also increasing cognitive and illness prevention. Swarnaprashana has numerous effects and can be given to children for better overall growth and development.